A comparative analysis of the umami taste of five fresh edible mushrooms by simulating the chemical environment of oral digestion in vitro. (15th February 2023) - Zhao, Jin; Wang, Tao; Zhang, Chen; Han, Xing; Yan, Junjie; Gan, Bingcheng
Abstract: This study aimed to explore the umami taste of five edible mushrooms ( Morchella esculenta, Pleurotus eryngii, Oudemansiella radicata, Lentinus edodes, and Grifola frondosa ). The substrates digested in a simulated oral chemical environment were analyzed for their umami taste compounds. Results showed that monosodium glutamate (MSG)-like amino acids (15.92 ± 0.42 mg/g) were highest in O. radicata, while P. eryngii had the maximum concentration of total 5′-nucleotide content (42.72 ± 0.95 mg/g) and flavor 5′-nucleotides (11.73 ± 0.10 mg/g). In addition, the equivalent umami concentration ranged from 232.96 ± 8.32 to 901.02 ± 17.39 g MSG/g dry weight, which revealed that P. eryngii and O. radicata exhibited a high level of umami taste. The reactions to proximate components were tested. P. eryngii exhibited the highest amount (mg/g dry weight) of soluble sugars (524.78 ± 50.05), whereas the lowest contents were recorded in O. radicata (97.64 ± 5.65). Our findings suggest that compared to the other three edible mushrooms, P. eryngii and O. radicata have a comparatively high umami taste value, and their primary umami constituents are, respectively, flavor 5′-nucleotides and umami amino acids. Highlights: A novelty method, boiling and salivary digestion, is applied to fresh mushrooms. The proximate composition of fresh mushrooms after saliva digestion was determined. P. eryngii and O. radicata have a comparatively high umami taste value. Flavor 5′-nucleotides are the main umami substances of P. eryngii. Umami amino acids are the main umami substances of O. radicata.